2008
DOI: 10.1080/10641190802022478
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility Characteristics of Korean Marine Clay

Abstract: A number of large-scale reclamations have taken place in the coastal areas of Korea. Very thick soft ground composed of marine clayey deposits is distributed along the coastal areas of Korea. More and more ground improvement has been conducted due to the rapid development of infrastructure and housing projects. As the consolidation behavioral parameters are required for the design of reclamation, the compressibility characteristics of four marine deposits were investigated by means of one-dimensional consolida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…For all three clays, C αe increases with the increase in the consolidation stress regardless of the sampling angle and reaches a maximum at a stress about twice the preconsolidation pressure; thereafter, C αe decreases irrespective of clay sample or sampling angle. This observation is consistent with previous studies (Mesri and Godlewski, 1977;Suneel et al, 2008) on various clays in the vertical direction.…”
Section: Secondary Compressionsupporting
confidence: 83%
“…For all three clays, C αe increases with the increase in the consolidation stress regardless of the sampling angle and reaches a maximum at a stress about twice the preconsolidation pressure; thereafter, C αe decreases irrespective of clay sample or sampling angle. This observation is consistent with previous studies (Mesri and Godlewski, 1977;Suneel et al, 2008) on various clays in the vertical direction.…”
Section: Secondary Compressionsupporting
confidence: 83%
“…This divergence about the relationship between Cαe and Cc could be related to the applied vertical stress range values, i.e., it is more likely to observe a convex relationship at high vertical stresses. Whatever is the shape of this relationship, the Cαe/Cc ratio was found to be constant during the tests 5,17,20,[23][24][25] .…”
Section: Introductionmentioning
confidence: 90%
“…The creep coefficient Cαe is both time and stress dependent 5,[12][13][14][15][16][17] . Suneel et al 17 showed that the creep strain increases with increasing effective stress in normally consolidated state. In addition, the value of Cαe is related to other soil parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that C ae either increases with the effective stress until the yield/ preconsolidation pressure and remains constant thereafter [18,33] or increases almost linearly with increasing effective stress [21]. Additionally, there have been some studies on the influence of the physical properties on the C ae [1,53,58,70,77,81]. However, many geotechnical correlations can only be applied in specific soil conditions and only for the limited soil types or regions of the occurrence.…”
Section: Introductionmentioning
confidence: 99%